Modulation of Antibody Responses to the V1V2 and V3 Regions of HIV-1 Envelope by Immune Complex Vaccines - Hioe, Catarina E.; Kumar, Rajnish; Upadhyay, Chitra; Jan, Muzafar; Fox, Alisa; Itri, Vincenza; Peachman, Kristina K.; Rao, Mangala; Liu, Lily; Lo, Nathan C.; Tuen, Michael; Jiang, Xunqing; et al. (Frontiers in Immunology, 2018)
Prophylactic HIV vaccines must elicit antibodies (Abs) against the virus envelope glycoproteins (Env) to effectively prevent HIV infection. We investigated a vaccine platform that utilizes immune complexes made of Env proteins gp120 and monoclonal Abs (mAbs) against different gp120 epitopes. We previously observed alterations in V3 antigenicity upon formation of certain gp120/mAb complexes and demonstrated the ability of these complexes to modulate the elicitation of V3 Ab responses. However, the effects on the V1V2 domain, an important target for Abs that correlate with vaccine-induced protection against HIV, have not been studied, nor have immune complex vaccines made with non-B subtype Env. This study compared subtypes B (JRFL) and CRF_01.AE (A244) Env gp120 proteins in complex with selected gp120-specific mAbs. Allosteric and antigenic changes were detected on these immune complexes, indicating that gp120/mAb interaction induces alterations on the Env surface that may modify the Env immunogenic properties. To evaluate this idea, mice were immunized with gp120/mAb complexes or their uncomplexed gp120 counterparts. The overall serum IgG titers elicited against gp120 were comparable, but a marked skewing toward V1V2 or V3 was evident and dependent on the gp120 strain and the specificity of the mAb used to form the complexes. Compared with uncomplexed gp120JRFL, gp120JRFL complexed with CD4bs or V1V2 mAbs, but not with C2 or V3 mAbs, elicited V3 Abs of greater titers and breadth, and Abs more capable of neutralizing tier 1 virus. Epitope mapping revealed a shift to a more conserved site in the V3 crown. However, the complexes did not enhance V1V2 Ab response, and the elicited V1V2 Abs were not cross-reactive. This profile contrasts with Ab responses to gp120A244/mAb complexes. Notably, gp120A244/mAb complexes induced higher levels of V1V2 Abs with some cross-reactivity, while also stimulating weak or strain-specific V3 Abs. Sera from gp120A244/mAb complex-immunized animals displayed no measurable virus neutralization but did mediate Ab-dependent cellular phagocytosis, albeit at levels similar to that induced by gp120A244 alone. These data indicate the potential utility of immune complexes as vaccines to shape Ab responses toward or away from Env sites of interest.